Rectocervical Fistula Repair After Laparoscopic Supracervical Hysterectomy and Laparoscopic Sacrocervicopexy - Havir, Martin; Ismail, Khaled M; Smazinka, Martin; Kalis, Vladimir; Rusavy, Zdenek (International urogynecology journal, 2025)
INTRODUCTION AND HYPOTHESIS: Rectocervical fistula after a urogynecological surgery has never been described. In this video article, we present occurrence of this complication after laparoscopic supracervical hysterectomy and laparoscopic sacrocervicopexy (LSCH + LSC) and how it was treated. METHODS: This was a case of a 47-year-old patient who had a laparoscopic supracervical hysterectomy and laparoscopic sacrocervicopexy (LSCH + LSC) for stage two pelvic organ prolapse. Within 3 months after the surgery, the patient complained of an odorous brownish vaginal discharge. On examination, this discharge was identified to be from the cervical canal. A provisional diagnosis of a rectocervical fistula was postulated and later confirmed by ultrasonography and colonoscopy. Consequently, a laparoscopic fistula repair with concomitant partial explantation of the mesh followed by removal of the cervix and transposition of an omental flap between the vaginal and rectal suture lines. The patient made an uneventful recovery. The resulting rectocele was repaired by a colpoperineorrhaphy 2 years after the surgery. CONCLUSION: Rectocervical fistula is a rare complication after laparoscopic sacrocervicopexy with concomitant supracervical hysterectomy. We demonstrated the feasibility of repairing this fistula laparoscopically. We opted for mesh explantation and removal of the cervix at the time of the fistula repair to mitigate the risk of recurrence.
Keywords: hysterektomie; prolaps pánevních orgánů; Postoperative Complications; Intestinal Fistula; gynekologické chirurgické výkony; rektální píštěl; Mesh explantation; nemoci cervix uteri; Gynecologic Surgical Procedures; laparoskopie; pooperační komplikace; Rectal Fistula; Pelvic Organ Prolapse; střevní píštěle; Supracervical hysterectomy; Hysterectomy; lidé; ženské pohlaví; Humans; cervix uteri; Uterine Cervical Diseases; Sacrocolpopexy; Rectocervical fistula; Laparoscopy; Female; lidé středního věku; Cervix Uteri; Middle Aged